2017
DOI: 10.1111/resp.13184
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Glasgow prognostic score in patients with acute exacerbation of idiopathic pulmonary fibrosis

Abstract: GPS can be helpful in predicting mortality in IPF patients with AE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
2
16
0
Order By: Relevance
“…A total of five studies reported PaO 2 /FiO 2 ratio using multivariate analysis. PaO 2 /FiO 2 ratio was demonstrated to be significantly associated with all-cause mortality in four studies with ORs of 0.99 (95% CI 0.98 to 1.00) 47 and 0.99 (95% CI 0.99 to 1.00) 59 and HRs of 0.99 (95% CI 0.99 to 1.00) 51 and 0.31 (95% CI 0.14 to 0.67) 64 , respectively. In another Open access Figure 2 Forest plot of the result of univariate analysis for partial pressure of arterial oxygen/fraction of inspired oxygen (PaO 2 / FiO 2 ) ratio (combined by HR).…”
Section: Discussionmentioning
confidence: 96%
“…A total of five studies reported PaO 2 /FiO 2 ratio using multivariate analysis. PaO 2 /FiO 2 ratio was demonstrated to be significantly associated with all-cause mortality in four studies with ORs of 0.99 (95% CI 0.98 to 1.00) 47 and 0.99 (95% CI 0.99 to 1.00) 59 and HRs of 0.99 (95% CI 0.99 to 1.00) 51 and 0.31 (95% CI 0.14 to 0.67) 64 , respectively. In another Open access Figure 2 Forest plot of the result of univariate analysis for partial pressure of arterial oxygen/fraction of inspired oxygen (PaO 2 / FiO 2 ) ratio (combined by HR).…”
Section: Discussionmentioning
confidence: 96%
“…AE‐IPF is a life‐threatening event; the 90‐day survival rate ranged from approximately 20% to 70% . Although the reported short‐term survival rate is variable, it likely depends on differences in the diagnostic criteria of AE‐IPF, baseline characteristics of the study population, study design and supportive therapy, among others.…”
Section: Discussionmentioning
confidence: 99%
“…A historically controlled study was conducted in AE‐IPF patients comparing patients who received the recombinant human soluble thrombomodulin (rhTM) to those who did not allow to consider the addition of rhTM to conventional treatment in future studies because of the improved overall survival. Also, the prognostic significance of Glasgow Coma Scale (GCS) has been proved to help predict mortality in AE‐IPF probably as it is representative of the host immune response.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 99%